THE ROLE OF COMPANY FINANCIAL STATEMENT DISCLOSURE TO ANTICIPATE BANKRUPTCY AND ITS IMPACT - I Nyoman Bontot; Martino Wibowo; Sippavitch Wongsuwatt (Samā Jiva Jnānam (International Journal of Social Studies), 2024)
Bankruptcy of a company not only harms the founders, shareholders (investors), suppliers and employees. Bankruptcy of a company can have a systemic impact on the economy of a country or even the global economy. Bankruptcy of a company can be caused by management errors and can also be caused by an economic/financial crisis that has hit. In fact, bankruptcy can be detected through analysis using a bankruptcy model. The data analyzed comes from the company's financial reports. This paper aims to examine the role of company disclosure on bankruptcy anticipation and the impact it has. Disclosure of company financial information is very important in anticipating bankruptcy, because early detection can be done to overcome it.